CHARACTER FORMATION OF BULLYING VICTIM STUDENTS WITH A PSYCHOEDUCATIONAL APPROACH - Nur Qamariah; Ganjar Muhammad Ganeswara (P3I UMSurabaya, 2024)
Bullying in schools has become a serious concern due to its negative impact on students' mental, emotional, and social development. This phenomenon hinders learning, damages character, and can lead to long-term psychological issues. This study employs a literature review approach to explore effective strategies for preventing bullying, particularly through psychoeducation. Psychoeducation plays a crucial role in helping students recognize bullying, manage emotions, develop social skills, and restore self-confidence. This approach also encourages students to internalize moral values and act responsibly. The analysis reveals that psychoeducation not only supports the recovery of victims but also creates a conducive school environment free from violence and promotes character building. Implementing psychoeducation is expected to break the cycle of bullying and produce a generation that is more empathetic, caring, and inclusive.